Cancellation of The Marriage Agreement Dedicated After The Marriage is Conducted - Habib Adjie; Benny Aji Prasetyo (Faculty of Law, Merdeka University Surabaya, 2021)
Marriage aims to form a happy, eternal, and conscious family without pressure. From a marital relationship, rights and obligations, including property, are regulated in the marriage law. For certain couples, marital property needs to be separated and a special agreement is made that regulates the separation of assets and obligations of both partners. In the case that it was found that there was a couple who made a separation agreement made after the marriage took place, there is a fact that the agreement was requested to be canceled for various reasons from the plaintiff. With these facts, the purpose of this study is to examine the legal aspects of the cancellation of the marriage agreement made after the marriage took place. This research method used a normative juridical method with a conceptual approach and legislation. The conclusion of this study is that marriage is a form of relationship between a man and a woman with the aim of forming a family, that it is undeniable that marriages are carried out between Indonesian citizens and foreigners and this is that there are legal differences that apply to men and women in mixed marriages because of differences in nationality. . In mixed marriages, there will be things regarding property that are different from marriages between Indonesian citizens and Indonesian citizens. The marriage agreement made by the couple before the marriage can be in the form of an authentic deed made before a notary as a public official, if the marriage agreement is made after the marriage it will result in null and void.